COMPUTER SIMULATIONS AS A TOOL FOR ENHANCING ALGEBRA RETENTION IN JUNIOR SECONDARY SCHOOLS: AN ANALYSIS - Ogala, Justin Onyarin; Okeoghene, Ohoriemu Blessing (FUDMA JOURNAL OF SCIENCES, 2024)
Over the years, Nigerian students have consistently performed poorly in mathematics. The West African Examination Council (WAEC) reports a steady decline in math performance among examinees outside the school system. Research papers and Chief Examiners' Reports have highlighted that students struggle with certain math tasks, indicating general deficiencies in mathematical skills. This research aimed to investigate the impact of computer simulation on students' retention of algebraic mathematics. The study was guided by two research questions and two hypotheses. A quasi-experimental design was employed, involving fifty-four students from two different schools. Each school had two junior secondary streams, with experimental and control groups assigned randomly. The lessons were conducted by the students' regular math teachers, who also served as research assistants. The Algebra Achievement Test (AAT) was used to measure retention, with a reliability coefficient 0.98. Data analysis was performed using SPSS software, with a significance level set at 0.05. The results revealed no statistically significant differences in the mean retention scores of male and female students who received algebra instruction through computer simulation.
Keywords: Algebraic Mathematics; Retention; Computer Simulation; Gender; Quasi-Experimental Design